Narratives of university women who participate in feminist collectives and their construction as socio-political subjects - Brito Rodríguez, Sonia; Basualto Porra, Lorena; Azócar González, Rodrigo; Flores Rivas, Claudia (Política y Sociedad, 2024)
The purpose of the article is to analyze the narratives of female university students belonging to feminist collectives, evidencing the discourses and norms that support their social practices from cultural breaks and continuities, positioning them as subjects of sociopolitical transformations. The research is carried out from a qualitative approach through an intertextual methodology of analysis of the stories obtained through semi-structured interviews applied to discussion groups. The participants are university women who belong to university feminist groups from higher education institutions in the various regions of the country that actively participated in the feminist May 2018. The results of the research refer to their own understanding of Chilean university feminist groups valuing themselves as historical and political subjects who have provoked a revolution in Chilean university spaces denouncing gender violence and building safer spaces for future generations. At the same time, they make these groups visible as an instance of empowerment of women who carry out sociopolitical advocacy in order to contribute to the construction of a more egalitarian and equitable Chilean society.